"All the Different Pieces of Me Being Integrated": Religion/Spirituality and Identity in Working Christian Mothers. Issue 2 (June 2022) - Laney, Elizabeth K.; Carruthers, Lisa A.; Hall, M. Elizabeth Lewis; Anderson, Tamara L.
The current qualitative study explored experiences of religion/spirituality and their impact on women's identities among Christian working mothers in academia. Thirty semi-structured interviews were conducted and the data analyzed using the grounded theory method. The resultant themes reflected the roles and functions of religion/spirituality in women's lives and in their identities, primarily by establishing a core sense of self that unified all of their roles and "selves." Religion/spirituality also served as meaning-making frameworks that provided purpose both to the self and to each of the women's roles, while religion/spirituality also pervaded every aspect of the self, coloring women's experience and driving their decisions. Further, women discussed religion/spirituality providing a sense of purpose by which they could pursue actualization and transcendence through generative means in each of their roles. The results indicate that spiritual identity may be a broader and more fundamental element of identity than previously considered. Implications of the current data and suggestions for future research are discussed.